Impact of EMIC Waves on Electron Flux Dropouts Measured by GPS Spacecraft: Insights From ELFIN - Mourenas, Didier; Artemyev, Anton V.; Zhang, Xiao‐Jia; Angelopoulos, Vassilis (Journal of geophysical research. Space physics, 2024)
Although the effects of electromagnetic ion cyclotron (EMIC) waves on the dynamics of the Earth's outer radiation belt have been a topic of intense research for more than 20 years, their influence on rapid dropouts of electron flux has not yet been fully assessed. Here, we make use of contemporaneous measurements on the same L $L$‐shell of trapped electron fluxes at 20,000 km altitude by Global Positioning System (GPS) spacecraft and of trapped and precipitating electron fluxes at 450 km altitude by Electron Losses and Fields Investigation (ELFIN) CubeSats in 2020–2022, to investigate the impact of EMIC wave‐driven electron precipitation on the dynamics of the outer radiation belt below the last closed drift shell of trapped electrons. During six of the seven selected events, the strong 1–2 MeV electron precipitation measured at ELFIN, likely driven by EMIC waves, occurs within 1–2 hr from a dropout of relativistic electron flux at GPS spacecraft. Using quasi‐linear diffusion theory, EMIC wave‐driven pitch angle diffusion rates are inferred from ELFIN measurements, allowing us to quantitatively estimate the corresponding flux drop based on typical spatial and temporal extents of EMIC waves. We find that EMIC wave‐driven electron precipitation alone can account for the observed dropout magnitude at 1.5–3 MeV during all events and that, when dropouts extend down to 0.5 MeV, a fraction of electron loss may sometimes be due to EMIC waves. This suggests that EMIC wave‐driven electron precipitation could modulate dropout magnitude above 1 MeV in the heart of the outer radiation belt. Key Points Electron precipitation likely driven by electromagnetic ion cyclotron (EMIC) waves is observed within 1–2 hr of electron flux dropouts Pitch angle diffusion rates inferred from low altitude measurements allow estimating the contribution of EMIC wave‐driven losses to dropouts EMIC wave‐driven electron precipitation could significantly modulate electron flux dropouts above 1.5 MeV and sometimes down to 0.5 MeV